Endoscopic Transorbital Approach to the Middle Fossa: Qualitative and Quantitative Anatomic Study. Issue 4 (6th October 2022) - Guizzardi, Giulia; Mosteiro, Alejandra; Hoyos, Jhon; Ferres, Abel; Topczewski, Thomaz; Reyes, Luis; Alobid, Isam; Matas, Jessica; Cavallo, Luigi Maria; Cappabianca, Paolo; Enseñat, Joaquim; Prats-Galino, Alberto; et al.
Abstract : BACKGROUND: The endoscopic superior eyelid transorbital route to the skull base is gaining progressive popularity in the neurosurgical community. OBJECTIVE: To evaluate the anatomy of the middle cranial fossa from this novel ventral perspective to reach the skull base through the transorbital route and to show limits for possible safe middle fossa drilling from the transorbital route. METHODS: Anatomic study was performed; 5 cadaveric specimens (ie, 10 sides) and 2 dry skulls (ie, 4 sides) were dissected. RESULTS: To obtain a functional result, there are boundaries that correspond to neurovascular structures that traverse, enter, or leave the middle fossa that must be respected: inferiorly, the lateral pterygoid muscle; medially, the Gasserian ganglion and the lateral border of the foramen rotundum; laterally, the foramen spinosum with the middle meningeal artery; superiorly, the lesser sphenoid wing; posteriorly, the anterior border of the foramen ovale. Average bone resected was 6.49 ± 0.80 cm 3 which is the 63% of total middle fossa floor. The mean axial surgical length calculated was 3.85 cm (3.18-5.19 cm) while the mean sagittal surgical length was 5.23 cm (4.87-6.55 cm). The mean horizontal angle of approach was 38.14° (32.87°-45.63°), while the mean vertical angle of approach was 18.56° (10.81°-26.76°). CONCLUSION: Detailed anatomy of the middle cranial fossa is presented, and herewith we demonstrated that from the endoscopic superior eyelid transorbital approach removal of middle cranial fossa floor is possible when anatomic landmarks are respected. Abstract :